The new frontline: exploring the links between moral distress, moral resilience and mental health in healthcare workers during the COVID-19 pandemic - Spilg, Edward G.; Rushton, Cynda H.; Phillips, Jennifer L.; Kendzerska, Tetyana; Saad, Mysa; Gifford, Wendy; Gautam, Mamta; Bhatla, Rajiv; Edwards, Jodi D.; Quilty, Lena; Leveille, Chloe; Robillard, Rebecca (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Global health crises, such as the COVID-19 pandemic, confront healthcare workers (HCW) with increased exposure to potentially morally distressing events. The pandemic has provided an opportunity to explore the links between moral distress, moral resilience, and emergence of mental health symptoms in HCWs. Methods A total of 962 Canadian healthcare workers (88.4% female, 44.6 + 12.8 years old) completed an online survey during the first COVID-19 wave in Canada (between April 3rd and September 3rd, 2020). Respondents completed a series of validated scales assessing moral distress, perceived stress, anxiety, and depression symptoms, and moral resilience. Respondents were grouped based on exposure to patients who tested positive for COVID-19. In addition to descriptive statistics and analyses of covariance, multiple linear regression was used to evaluate if moral resilience moderates the association between exposure to morally distressing events and moral distress. Factors associated with moral resilience were also assessed. Findings Respondents working with patients with COVID-19 showed significantly more severe moral distress, anxiety, and depression symptoms (F > 5.5, p < .020), and a higher proportion screened positive for mental disorders (Chi-squared > 9.1, p = .002), compared to healthcare workers who were not. Moral resilience moderated the relationship between exposure to potentially morally distressing events and moral distress (p < .001); compared to those with higher moral resilience, the subgroup with the lowest moral resilience had a steeper cross-sectional worsening in moral distress as the frequency of potentially morally distressing events increased. Moral resilience also correlated with lower stress, anxiety, and depression symptoms (r > .27, p < .001). Factors independently associated with stronger moral resilience included: being male, older age, no mental disorder diagnosis, sleeping more, and higher support from employers and colleagues (B [0.02, |-0.26|]. Interpretation Elevated moral distress and mental health symptoms in healthcare workers facing a global crisis such as the COVID-19 pandemic call for the development of interventions promoting moral resilience as a protective measure against moral adversities.